2019
DOI: 10.1371/journal.pone.0208992
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and cost-effectiveness of endobronchial ultrasound-guided transbronchial needle aspiration for preoperative staging of non-small–cell lung cancer: Results of a French prospective multicenter trial (EVIEPEB)

Abstract: This two-step study evaluated the cost-effectiveness of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) for presurgery staging of non-small cell lung cancer (NSCLC) in France (EVIEPEB; ClinicalTrial.gov identifier NCT00960271).Step 1 consisted of a high-benchmark EBUS-TBNA–training program in participating hospital centers. Step 2 was a prospective, national, multicenter study on patients with confirmed or suspected NSCLC and an indication for mediastinal staging with at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…To estimate the underlying true rate of involved lymph node stations from the rate of EBUS-positive lymph node stations, a specificity of nearly 100% and a sensitivity of 80% of EBUS-TBNA were assumed throughout the present study. This is supported by several prospective [26][27][28][29][30][31][32] and large retrospective studies [33,34]. The SCORE study included 229 patients with known or suspected NSCLC [26].…”
Section: Discussionmentioning
confidence: 91%
“…To estimate the underlying true rate of involved lymph node stations from the rate of EBUS-positive lymph node stations, a specificity of nearly 100% and a sensitivity of 80% of EBUS-TBNA were assumed throughout the present study. This is supported by several prospective [26][27][28][29][30][31][32] and large retrospective studies [33,34]. The SCORE study included 229 patients with known or suspected NSCLC [26].…”
Section: Discussionmentioning
confidence: 91%
“…Additional systemic cost economy could be expected through shorter lengths of PACU stay and more efficient periprocedural patient flow management, although these metrics are difficult to quantify at the patient level. One major benefit of EBUS over mediastinoscopy is its cost-effectiveness and relatively lower costs, 7,9,10 and therefore a strategy for the implementation of EBUS-FNA should at least in part involve an effort to decrease unnecessary costs of care. Hundreds of thousands of EBUS-FNA procedures are performed annually in the United States, and this high volume of procedures underscores the potential for cost savings at a national level by using a minor alteration in postprocedure patient care.…”
Section: Commentmentioning
confidence: 99%
“…Fernandez et al observed that systematic mediastinoscopy was not cost-effective in patients with T1–2 N0 tumors and a SUV max higher than 10, since only 1 out of 90 patients had occult nodal metastases ( 12 ). The results of metabolic assessment may also influence the results of endoscopic staging, since Chouaid et al observed that the sensitivity and NPV of EBUS-TBNA were respectively 90.4% and 75.7% in patients with a positive PET scan and 83.3% and 96.6% in patients with negative PET scans ( 13 ). Other studies show that the accuracy of EBUS-TBNA is influenced by the use of preliminary non-invasive staging.…”
Section: Factors Influencing the Accuracy And Cost-effectiveness Of Surgical And Endoscopic Techniquesmentioning
confidence: 99%
“…Notably, 75% of the endoscopic procedures were performed under general anesthesia, a point in contrast with the results of the study by Czarnecka-Kujawa et al In fact, the Authors calculated that if all the procedures had been carried out under general anesthesia, an expected saving of €994 per patient would still have been observed. Conversely, no advantage would have been present if the costs of EBUS had been higher than €1,834 ( 13 ). In another study, Andrade et al compared the direct and indirect costs of mediastinoscopy and EBUS-TBNA.…”
Section: Impact Of Mediastinal Staging On Quality Of Life Costs and Treatmentmentioning
confidence: 99%